(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article explores the psychological measures that can be implemented to safeguard adolescents from information threats in the era of globalization. It discusses the importance of these measures, research methods to assess their effectiveness, presents the results of recent studies, and offers suggestions for parents, educators, and policymakers to enhance the protection of adolescents in the digital age